An extraordinary new fluvial bdelloid rotifer, Coronistomus impossibilis gen. nov., sp. nov., with adaptations for turbulent flow (Rotifera: Bdelloidea: Coronistomidae fam. nov.) - Örstan, Aydin (Zootaxa, 2021)
A new bdelloid rotifer, Coronistomus impossibilis gen. nov., sp. nov. is described from the Hawlings River in Maryland, USA. The new species is a non-swimming sediment dweller that exceeds 550 µm in body length. Its corona is a weakly bilobed ciliated field on the ventral side of the head with lateral borders continuing into mouth. The species has ramate trophi that have on each half three widely spaced major teeth with two interproximal teeth. The foot lacks spurs and ends with a pair of long, thick ventral toes and a medially positioned caudal appendage. The new species lives in microhabitats exposed to turbulent flow and its morphological idiosyncrasies are interpreted as adaptations to reduce the likelihood of getting dislodged by the water. Although the corona morphology and the caudal appendage of the new species are similar to the corresponding traits of some of the species in the family Philodinavidae, the structure of its nonprotrusible trophi and its possession of only two toes (as opposed to four) separate it from all other members of the Philodinavidae. Therefore, a new family, Coronistomidae fam. nov., is erected for the new genus Coronistomus.